Citizen Satisfaction in Public Services: A Descriptive and Explanatory Study in an Archipelagic Region - Johan Fahri; Hartaty Hadady (AIBPM Publisher, 2025)
Satisfaction has long been discussed in academic literature, although its interpretation varies depending on market structures and consumer conditions. Customer satisfaction generally refers to the evaluation made by customers after purchasing or using a product in a competitive market. However, in a monopoly context where consumers have limited choices, the concept shifts toward citizen satisfaction, particularly in relation to public services provided by the government. Public service delivery becomes more complex when geographical conditions are involved, especially in archipelagic regions. North Maluku Province represents one of Indonesia’s ocean-dominated regions, reflecting the characteristics of the country as the world’s largest archipelagic state. This study aims to analyze descriptively the level of citizen satisfaction with public services in North Maluku Province. Citizen satisfaction is considered a primary objective of government service delivery. Based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform (PAN-RB) No. 14 of 2017, nine service elements are used to measure public satisfaction. This study employs a quantitative deductive approach to examine the relationship between these elements and community satisfaction.